RETRACTED: Magnetic resonance imaging and 18F-fludeoxyglucose positron emission tomography/computed tomography findings of retroperitoneal clear cell carcinoma with an unknown primary site: A case report - Zeng, Dao-Bing; Chang, Chan; Liu, Xu-Sheng; Gao, Yan; Wang, Ya-Lan; Pei, Zhi-Jun (Frontiers in Medicine, 2022)
Herein, we report a case of retroperitoneal clear cell carcinoma (RCCC) with an unknown primary site that was confirmed via pathology. A 46-year-old man presented with low-grade fever, hyperhidrosis, and nightly fatigue that had occurred for the last 20 days. His weight had decreased significantly within the past 2 months (approximately 12 kg). On abdominal ultrasound, a mass was observed near the left renal hilum. In addition, enhanced magnetic resonance imaging (MRI) of the abdomen revealed a retroperitoneal nodular mass; however, no abnormalities in either kidney or adrenal glands were observed. 18F-fludeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) demonstrated an intensely FDG-avid retroperitoneal mass, the maximum standardized uptake value (SUVmax) was 19.6. On March 8, 2021, left retroperitoneal lesion resection, retroperitoneal lymph node dissection, and double kidney exploration were performed under general anesthesia. A post-operative pathological examination revealed Poorly differentiated clear cell carcinoma (left retroperitoneal) and metastatic lymph nodes. Immunohistochemical findings showed that the tumor originated from the kidney. At 6-month follow-up, reexamination of the patient revealed retroperitoneal lesion recurrence; however, no abnormalities were observable via enhanced computed tomography (CT) of both kidneys. To our knowledge, there have been no previous reports of RCCC of unknown origin.